Determinants and impact of masked hypertension in offspring of patients with diabetes: relation with coronary flow and cardiac function - Ragab A. Mahfouz; Mohammad Gouda; Waleed Alawady (Blood Pressure, 2019)
Objective: We aimed to evaluate the prevalence, determinants and clinical impact of masked hypertension in offspring of patients with diabetes. Masked hypertension was defined according to guidelines as daytime ambulatory blood pressure monitoring “ABPM” ≥135/85 mmHg and clinic BP <140/90 mmHg. Methods: 100 nondiabetic offspring of patients with diabetes and 60 offspring of healthy people were enrolled; 24-h ABPM was applied to evaluate mean 24-h systolic/diastolic blood pressure “BP”, daytime, nighttime and night dipping readings. Left ventricular parameters and coronary flow reserve of the left anterior descending artery (induced by adenosine 0.14 mg/kg/min) was calculated in all offspring. Results: 29% of offspring of patients with diabetes had masked hypertension compared to only 3.3% offspring in healthy people (p < 0.001). Compared with those without masked hypertension, offspring with masked hypertension had a significantly reduced coronary flow reserve (p < 0.001), significantly higher E/e' (p < 0.01), [a surrogate marker of left ventricular filling pressure], more microalbuminuria (p < 0.01), and higher values of high-sensitive C-reactive protein “CRP” (p < 0.001). Multivariate regression analysis showed that, fasting blood glucose, and high-sensitive CRP, were independently associated with masked hypertension, whilst daytime systolic BP and non-dipping systolic BP were the strongest predictors for masked hypertension. Logistic regression analysis revealed that masked hypertension was independently associated with reduced coronary flow reserve (p < 0.0001) and diastolic dysfunction (p < 0.001). Conclusion: Masked hypertension is prevalent in offspring of patients with diabetes and significantly associated with reduced coronary flow reserve and left ventricular diastolic dysfunction. These findings suggest that offspring of patients with diabetes constitute a high risk group and deserve close follow up, mainly with the use of ABPM.